Sustainable Development of the Worker Through Dignified Work - Pérez, Fabián Ojeda; García Bueno, Marco César; González Franco, Rubén Antonio (Sociedad y Economía, 2019)
The objective of the following research is to design a model of sustainable worker development from the perspective of decent work and human rights, based on the 2030 agenda for sustainable development, to eradicate social, economic and environmental problems. It is a documentary research with explanatory scope, carried out through the analysis of scientific articles and publications of international organizations. It is necessary for workers to have access to dignified and decent employment, since through it, they can participate equitably in the wealth generated, as well as obtaining access to quality healthcare and education services, and social security systems alike, and thus attaining a dignified life and self-realization, through time. Since sustainable development is part of the fundamental rights of the worker, the Constitution grants them legal protection and obliges the government to guarantee them.